FEASIBILITY ANALYSIS OF WINGED PEARL OYSTER (Pteria penguin) CULTIVATION BUSINESS IN PALABUSA WATER BAUBAU - Syah, Prima Insamilandari; Djai, Suhaiba; Ihsan, Fadhli Insani; T, Suhartin; Fitrianti, Fitrianti (Politeknik Kelautan dan Perikanan Dumai, 2025)
Mabe pearl oyster (Pteria penguin) cultivation has great potential as an alternative source of income for coastal communities through the production of high-value pearls and value-added by-products. This study aims to analyze the technical and financial feasibility of this cultivation in the waters of Palabusa, Baubau City, Southeast Sulawesi. The research employed a case study method using primary data collected through observation and interviews, and secondary data obtained from literature studies. Data were analyzed both technically and financially. The technical analysis showed that the geographic condition of Palabusa, which is surrounded by small islands, provides natural protection from large waves. Water quality parameters, including temperature (29–31°C), salinity (31–32 ppt), transparency (6–9 m), current velocity (0.22 m/s), depth (6–10 m), and seagrass–sandy substrate, were within the optimal range for pearl oyster cultivation. The applied longline culture system (6×6 m) achieved a high survival rate of 85%. Financial analysis revealed that an initial investment of IDR 166,500,000 for floating cages, boats, and equipment was highly feasible. The Net Present Value (NPV) was IDR 232,700,884 (at a 10% discount rate), Internal Rate of Return (IRR) 60% per year, and Payback Period (PP) 1.58 years ( 19 months). The Break-Even Point (BEP) was reached at 5,068 units or a selling price of IDR 9,645 per unit, generating a net profit of IDR 105,308,188 per cycle. The study concludes that mabe pearl oyster farming in Palabusa Waters is technically and financially feasible, offering high profitability and rapid investment returns, making it a promising and sustainable enterprise.